MCT2 mediates concentration-dependent inhibition of glutamine metabolism by MOG. (November 2018) - Fets, Louise; Driscoll, Paul; Grimm, Fiona; Jain, Aakriti; Nunes, Patrícia; Gounis, Michalis; Doglioni, Ginevra; Papageorgiou, George; Ragan, Timothy; Campos, Sebastien; Silva dos Santos, Mariana; MacRae, James; et al.
Abstract α-Ketoglutarate (αKG) is a key node in many important metabolic pathways. The αKG analog N-oxalylglycine (NOG) and its cell-permeable prodrug dimethyloxalylglycine (DMOG) are extensively used to inhibit αKG-dependent dioxygenases. However, whether NOG interference with other αKG-dependent processes contributes to its mode of action remains poorly understood. Here we show that, in aqueous solutions, DMOG is rapidly hydrolyzed, yielding methyloxalylglycine (MOG). MOG elicits cytotoxicity in a manner that depends on its transport by monocarboxylate transporter 2 (MCT2) and is associated with decreased glutamine-derived tricarboxylic acid–cycle flux, suppressed mitochondrial respiration and decreased ATP production. MCT2-facilitated entry of MOG into cells leads to sufficiently high concentrations of NOG to inhibit multiple enzymes in glutamine metabolism, including glutamate dehydrogenase. These findings reveal that MCT2 dictates the mode of action of NOG by determining its intracellular concentration and have important implications for the use of (D)MOG in studying αKG-dependent signaling and metabolism. High intracellular concentrations of the α-ketoglutarate analog N-oxalylglycine, owing to MCT2-mediated transport of its newly described prodrug MOG, inhibit multiple enzymes in glutamine metabolism and selectively kill MCT2-expressing cancer cells.